Studi Kualitas Layanan dan Kepuasan Masyarakat terhadap Layanan Administrasi Dapodik di Dinas Pendidikan dan Kebudayaan Kota Bontang - Marsudi Marsudi; Fajar Apriani; Hariati Hariati (Nakhoda: Jurnal Ilmu Pemerintahan, 2026)
This study examines public satisfaction with the Core Education Data System (Dapodik) administrative services at the Bontang City Education and Culture Office, focusing on the factors that shape user perceptions and the service-quality dimensions most in need of improvement. Using a quantitative descriptive design with an evaluative survey approach, the study applies the Public Satisfaction Survey (SKM) framework established under Regulation of the Minister of Administrative and Bureaucratic Reform of the Republic of Indonesia No. 14 of 2017, integrated with the SERVQUAL model’s five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected from 152 school operators across various educational levels via a structured questionnaire distributed through Google Forms, using a four-point Likert scale (1 = dissatisfied to 4 = very satisfied) and a proportional quota sampling method. Statistical analysis comprised the SKM computational model for satisfaction indexing, descriptive statistics for indicator-level scores, and multiple linear regression to identify the most influential service-quality predictors. The overall satisfaction index falls in the “Good” (Baik) category, indicating that while the service system and technology function adequately, several service dimensions have not yet met user expectations. Among the nine service indicators, assurance and competence scored highest, reflecting users’ confidence in staff professionalism and reliability, while responsiveness, reliability, and complaint handling scored lowest, pointing to delays and inconsistency in service delivery. The study concludes that improving Dapodik users’ satisfaction requires more than procedural and technological gains: continued attention to responsiveness and empathy in service delivery is essential.